Dietary nitrate supplementation does not improve resistance exercise performance in resistance-trained women - Sydney N. Brennan; Justin M. Foster; Raymond T. Gerardo; Trevor J. Molnar; Ryan Tran; Christopher B. Sottile; Kyle S. Geppert; Michael Egiazarian; Abigail F. Ballhagen; Money Ghimire; John R. M. Renwick; Lewis A. Gough; et al. (European Journal of Applied Physiology, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

A perfluoro-functionalised fluorescent maleimide probe for imaging of per- and polyfluoroalkyl substances - Jake E. Barker; Stephen D. P. Fielden; Richard H. Kempton; Calum T. J. Ferguson; Rachel K. O’Reilly; Grant B. Douglas (Environmental Chemistry Letters, 2026)
The persistence of per- and polyfluoroalkyl substances in the environment is becoming a major health concern, yet studying their fate and behaviour in complex media is limited due to the lack of suitable analytical methods. Here we proposed that a fluorescent polyfluoroalkyl probe could enable rapid tracing and negate drawbacks associated with current techniques. We synthesised a fluorescent probe containing a maleimide motif grafted to perfluorooctanoic acid. Using a conductivity assay, the critical micelle concentration was determined, and cryogenic transmission electron microscopy was further utilised to verify the presence of multilamellar vesicles. Titration of the fluorescent probe with a base enabled the determination of the acid dissociation constant, an important property of perfluorooctanoic acid. Results show that this fluorescent probe exhibits similar properties to perfluorooctanoic acid, and thus could reasonably act as an environmental proxy, with the benefit of strong, concentration-dependent and environmentally responsive fluorescence. This fluorescence offers a facile entry point for real-time tracing in various media. Further exploration of this tracer through plant, concrete, or soil studies could enable a better understanding of per- and polyfluoroalkyl substance behaviour in range of natural and artificial media.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Changes in Key Biodiversity Area networks following national comprehensive assessments - Andrew J. Plumptre; Zoltan Waliczky; Daniele Baisero; Olivia Crowe; Jeannot Kivono; Cecilia Tobar; Maria Gabriela Toscano; Natalia Boulad; Hugo Costa; Camila Davila; Sophie Dirou; Eleuterio Duarte; et al. (Conservation Biology, 2026)
Key Biodiversity Areas (KBAs) are sites of significance for the global persistence of biodiversity. Based on the Global Standard for the Identification of Key Biodiversity Areas (KBA Standard), published in 2016, sites are currently being assessed for KBA designation in a growing number of countries across the world. For these assessments, the KBA criteria are applied to all species and ecosystems with available data. We reviewed the first comprehensive assessments of 11 countries and compared the KBA network before and after assessments. The mean (SD) number of KBAs per country increased by 69.6% (102.1), and the mean total extent of KBAs per country increased by 164.2% (150.7). More than half of the KBAs in 2024 had >50% of their area outside the 2019 KBAs, indicating a substantial increase in KBA extent (54.0% [18.8] of KBAs). The mean proportion of each KBA covered by protected or conserved areas decreased from 56.2% (20.2) to 44.5% (15.5), owing to the incorporation of unprotected sites in the KBA network. On average, 41.1% (14.0) of sites in each country (mean 44.5 [46.4] sites per country) and 47.2% (20.5) of new KBA area after the assessment were completely unprotected, indicating that many of the new sites were not recognized in national protected area networks as significant for biodiversity before the assessment. Making a comprehensive assessment of KBAs increased the combined coverage of protected and conserved area networks from 25.4% (10.6) to 32.0% (13.1) in each country and thus contributed to reducing biodiversity loss. Therefore, comprehensive assessments of KBAs led to a substantially increased number and extent of recognized sites of importance for biodiversity published in the World Database of KBAs. Where such assessments have not been made, many important areas for biodiversity may be overlooked. We therefore encourage other nations to update their KBA networks to inform efforts to meet the goals and targets of the Kunming–Montreal Global Biodiversity Framework.

Ten questions concerning indoor dust - Erica M. Hartmann; Karen C. Dannemiller; Delphine K. Farmer; Rachel E. O'Brien; Joseph Berberich; Jenna C. Ditto; Olivia R. Farinas; Elliott T. Gall; Anindita Ganguly; Vicki H. Grassian; Rachel Greene; Bridget Hegarty; et al. (Building and Environment, 2026)

Thermal infrared characterization of spatially unresolved resident space objects: Prospects from analytical two-component modeling - Stephen Catsamas; Sarah Caddy; Michele Trenti; Benjamin Metha; Simon Barraclough; Robert Mearns; Airlie Chapman; Rachel Webster (Advances in Space Research, 2026)

Bridging in vitro and in vivo inhalation toxicity: Volatile organic compounds elicit similar transcriptomic points of departure in human airway cells and mouse respiratory tract - Thomas W. Jackson; Jessica R. Murray; Celia M. Schacht; Paul A. Evansky; Michael E. Monsees; Joshua A. Harrill; M. Ian Gilmour; Andrew F. Johnstone; Wanda C. Williams; Rachel D. Grindstaff; Mette C. Schladweiler; Samuel A. Vance; et al. (Environmental Pollution, 2025)

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

Effects of residential ventilation and filtration interventions on adult asthma outcomes - Insung Kang; Anna McCreery; Parham Azimi; Mingyu Wang; Amanda Gramigna; Griselda Baca; Timothy Crowder; Rachel Scheu; Anne Evens; Brent Stephens (Building and Environment, 2025)

The effect of dietary nitrate supplementation on resistance exercise performance: A dose–response investigation - Rachel Tan; Isabella G. Lincoln; Keonabelle K. Paniagua; Justin M. Foster; Lauren E. Wideen; Raymond T. Gerardo; Nathan J. Ornelas; Isaac Tchaprazian; Jeffrey Li; Michael Egiazarian; Samantha N. Rowland; Stephen J. Bailey; et al. (European Journal of Applied Physiology, 2025)
Dietary nitrate (NO 3 − ) can enhance skeletal muscle contractile function and explosive-type exercise by modulating type II muscle fibers; however, limited attention has been directed at exploring the optimal dosing guidelines and potential performance-enhancing effects of NO 3 − supplementation during resistance-type exercise. The purpose of our investigation was to examine potential dose–response effects of concentrated NO 3 − -rich beetroot juice on neuromuscular performance during resistance exercise. Eighteen resistance-trained men were assigned in a double-blind, randomized, crossover design, to four conditions to consume beetroot juice containing: negligible NO 3 − (PL); ~ 6 mmol NO 3 − (BR-LOW); ~ 12 mmol NO 3 − (BR-MOD); and ~ 24 mmol NO 3 − (BR-HIGH). Participants completed 1 set of vertical countermovement jumps (CMJ), 2 sets × 3 repetitions of barbell back squats, and 2 sets × 3 repetitions of barbell bench press 2.5 h post-supplementation. Plasma [NO 3 − ] increased in a dose-dependent manner ( P < 0.01). Plasma [nitrite] ([NO 2 − ]) increased in all BR conditions compared to PL ( P < 0.05), such that BR-MOD vs. BR-LOW ( P < 0.01) and BR-LOW vs. PL ( P < 0.01), but BR-HIGH was not different compared to BR-MOD ( P > 0.05). Performance was not different between conditions in CMJ, 50% one-repetition maximum (1RM) and 75%1RM back squats, or 50%1RM and 75%1RM bench press ( P > 0.05). The change in plasma [NO 2 − ] was significantly correlated with peak power ( r = − 0.65, P = 0.003), mean power ( r = − 0.52, P = 0.03), and mean velocity ( r = − 0.48, P = 0.04) during 50%1RM back squats following BR-LOW vs. PL but not in other conditions ( P > 0.05). This study indicates that dietary NO 3 − does not impact resistance exercise performance at any of the doses assessed in the current study.

Habitat Conversion by Native Spartina Highlights the Importance of Wetland Restoration Design Relative to Site-Specific Vertical Range of Vegetation - Rachel S. Smith; Emily Blair; Andres Deza; Justin C. Hoesterey; David Huang; Russell Johnston; Henry M. Page; Stephen C. Schroeter; Morgan Tusa; Denise Weisman; Kathryn M. Beheshti (Estuaries and Coasts, 2025)
Native vegetation is planted in wetland restoration projects to supplement natural recruitment and achieve a habitat mix that supports ecological functioning. The native cordgrass Spartina foliosa —an ecosystem engineer with a wide elevation range—is frequently planted in wetland restorations in Southern California to jumpstart low marsh development. Although plantings can increase vegetation cover, planted S. foliosa can also convert areas designed as tidal creeks or mudflat to salt marsh, hindering progress towards restoration objectives. At the restored San Dieguito Wetlands (SDW) in Southern California , S. foliosa was planted during (2008–2009) and after wetland construction (2011–2018). In 2023, S. foliosa occupied 10.8 ha at SDW, but had converted 42% of built tidal creek and mudflat habitat to salt marsh. Genetic testing ruled out potential hybridization with non-native Spartina . Tidal creek elevations were higher at SDW than at other California wetlands, overlapping with the design elevation of low marsh for the site. Spartina foliosa extended to lower elevations at SDW than other California wetlands, overlapping with the design elevation of mudflat for the site. Thus, habitat conversion at SDW was likely due to insufficient excavation of built tidal creeks and the lower than expected elevation range of S. foliosa at the site. Much of the existing tidal creek and mudflat habitat at SDW is likely susceptible to habitat conversion to salt marsh. Our results emphasize the need to consider the design elevation of restored habitats relative to site-specific elevation ranges of target wetland species.

Forest Age Rivals Climate to Explain Reproductive Allocation Patterns in Forest Ecosystems Globally - Rachel E. Ward; Huanyuan Zhang‐Zheng; Kate Abernethy; Stephen Adu‐Bredu; Luzmilla Arroyo; Andrew Bailey; Jos Barlow; Erika Berenguer; Liana Chesini‐Rossi; Percival Cho; Cecilia A. L. Dahlsjö; Eder Carvalho das Neves; et al. (Ecology Letters, 2025)
Forest allocation of net primary productivity (NPP) to reproduction (carbon required for flowers, fruits, and seeds) is poorly quantified globally, despite its critical role in forest regeneration and a well‐supported trade‐off with allocation to growth. Here, we present the first global synthesis of a biometric proxy for forest reproductive allocation (RA) across environmental and stand age gradients from a compiled dataset of 824 observations across 393 sites. We find that ecosystem‐scale RA increases ~60% from boreal to tropical forests. Climate shows important non‐linear relationships with RA, but is not the sole predictor. Forest age effects are comparable to climate in magnitude (MAT: ß = 0.24, p = 0.021; old growth forest: ß = 0.22, p p = 0.001; soil N: ß = −0.07, p = 0.001). These results provide strong evidence that ecosystem‐scale RA is mediated by climate, forest age, and soil conditions, and is not a globally fixed fraction of positive NPP as assumed by most vegetation and ecosystem models. Our dataset and findings can be used by modellers to improve predictions of forest regeneration and carbon cycling.

Assessing changes between two years in macrobenthic invertebrate communities in four sub-tropical Australian estuaries - Muhammad M. Islami; Adam Davey; Stephen D.A. Smith; Victoria J. Cole; Rachel Przeslawski; Kirsten Benkendorff (Regional Studies in Marine Science, 2025)

Genome-wide association analysis identifies seven loci conferring resistance to multiple wheat foliar diseases, including brown and yellow rust resistance originating from Aegilops ventricosa - Keith A. Gardner; Bethany Love; Pauline Bansept-Basler; Tobias Barber; Simon Berry; Nick Bird; Finn Borum; Lesley Boyd; James K. M. Brown; Ruth Bryant; Paul Fenwick; David Feuerhelm; et al. (Theoretical and Applied Genetics, 2025)
We assembled a European bread wheat ( Triticum aestivum L.) association mapping panel ( n = 480) genotyped using a 90,000 feature single nucleotide polymorphism array, with the aim of identifying genetic loci controlling resistance to four fungal diseases: yellow (stripe) rust (YR), brown (leaf) rust (BR), Septoria tritici blotch (ST) and powdery mildew (PM). Simulations showed our panel to have good power to detect genetic loci, with > 50% probability of identifying loci controlling as little as 5% of the variance when heritability was 0.6 or more. Using disease infection data collected across 31 trials undertaken in five European countries, genome-wide association studies (GWAS) identified 34 replicated genetic loci (20 for YR, 12 for BR, two for PM, 0 for ST), with seven loci associated with resistance to two or more diseases. Construction and analysis of eight bi-parental populations enabled two selected genetic loci, yellow rust resistance locus YR_2A010 (chromosome 2A) and YR_6A610 (6A), to be independently cross-validated, along with the development of genetic markers to track resistance alleles at these loci. Notably, the chromosome 2A yellow and brown rust resistance locus corresponds to the 2N v S introgression from the wild wheat species, Aegilops ventricosa . We found evidence of strong selection for 2N v S over recent breeding history, being present in 48% of the most recent cultivars in our panel. Collectively, we define the genetic architectures controlling resistance to major fungal diseases of wheat under European field environments, and provide resources to exploit these for the development of new wheat cultivars with improved disease resistance.

An abundant non-native freshwater copepod, Arctodiaptomus dorsalis, on the Island of Hawai‘i: distribution, dominance, dispersal, and diapause - Nelson G. Hairston; Rachel L. Wilkins; Cheryl Ka‘uhane Lupenui; Stephen P. Ellner (Biological Invasions, 2025)

Testing for presence of alternative photosynthetic pathways in plants during the Mississippian - Tara A. Putri; Benjamin C. Gill; Stephen E. Scheckler; Rachel Reid (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

How accurate is your average? Considering error when counting sea lice on open-pen salmon farms - Alexes Mes; Jed Stephens; Matthew Palmer; Rachel Mulrenan; Corin Smith (Aquaculture, 2024)

Effectiveness of ozone nanobubble treatments on high biomass cyanobacterial blooms: A mesocosm experiment and field trial - Justin D. Chaffin; David E. Berthold; Eugene C. Braig; Josh D. Fuchs; Rachel S. Gabor; Stephen J. Jacquemin; Haley E. Kuhn; Lillian D. Labus; H. Dail Laughinghouse; Forrest W. Lefler; Heath E. Mash; Heather A. Raymond; et al. (Journal of Environmental Management, 2024)

Acute inorganic nitrate ingestion does not impact oral microbial composition, cognitive function, or high-intensity exercise performance in female team-sport athletes - Rachel Tan; Courtney Merrill; Chandler F. Riley; Maya A. Hammer; Ryan T. Kenney; Alyssa A. Riley; Jeffrey Li; Alexandra C. Zink; Sean T. Karl; Katherine M. Price; Luka K. Sharabidze; Samantha N. Rowland; et al. (European Journal of Applied Physiology, 2024)
The purpose of this study was to investigate the effects of acute nitrate (NO 3 − )-rich beetroot juice ingestion on explosive and high-intensity exercise performance, oral microbiota composition, and cognitive flexibility (i.e., function), before and after maximal intermittent running exercise. Fifteen women team-sport athletes were assigned in a randomized, double-blind, crossover design to consume concentrated NO 3 – -depleted beetroot juice (PL; 0.1 mmol NO 3 − ) and NO 3 − -rich beetroot juice (BR; 12.0 mmol NO 3 − ) 2.5 h prior to performing a battery of exercise performance tasks and cognitive testing before and after the Yo–Yo intermittent recovery level 1 (YYIR1) running test. Resting plasma [NO 3 − ] and plasma nitrite ([NO 2 − ]) were elevated following BR ( P < 0.001). BR did not impact global composition or relative abundance of taxa in the oral microbiome ( P > 0.05) or cognitive flexibility before or after exercise ( P > 0.05). There was no significant difference in performance during 20-m (PRE, PL: 4.38 ± 0.27 vs. BR: 4.38 ± 0.32 s; POST, PL: 4.45 ± 0.29 vs. BR: 4.43 ± 0.35 s) and 10-m sprints (PRE, PL 2.78 ± 0.15 vs. BR 2.79 ± 0.18 s; POST, PL: 2.82 ± 0.16 vs. BR: 2.81 ± 0.19 s), isokinetic handgrip dynamometry, medicine ball throw, horizontal countermovement jump, or YYIR1 (PL: 355 ± 163 m vs. BR: 368 ± 184 m) between BR and PL ( P > 0.05). These findings indicate that acute dietary NO 3 − may not influence the oral microbiome, explosive and high-intensity exercise performance, or cognitive function in women team-sport athletes.

Near‐Term Forecasting of Terrestrial Mobile Species Distributions for Adaptive Management Under Extreme Weather Events - Rachel Dobson; Stephen G. Willis; Stewart Jennings; Robert A. Cheke; Andrew J. Challinor; Martin Dallimer (Global Change Biology, 2024)
Across the globe, mobile species are key components of ecosystems. Migratory birds and nomadic antelope can have considerable conservation, economic or societal value, while irruptive insects can be major pests and threaten food security. Extreme weather events, which are increasing in frequency and intensity under ongoing climate change, are driving rapid and unforeseen shifts in mobile species distributions. This challenges their management, potentially leading to population declines, or exacerbating the adverse impacts of pests. Near‐term, within‐year forecasting may have the potential to anticipate mobile species distribution changes during extreme weather events, thus informing adaptive management strategies. Here, for the first time, we assess the robustness of near‐term forecasting of the distribution of a terrestrial species under extreme weather. For this, we generated near‐term (2 weeks to 7 months ahead) distribution forecasts for a crop pest that is a threat to food security in southern Africa, the red‐billed quelea Quelea quelea . To assess performance, we generated hindcasts of the species distribution across 13 years (2004–2016) that encompassed two major droughts. We show that, using dynamic species distribution models (D‐SDMs), environmental suitability for quelea can be accurately forecast with seasonal lead times (up to 7 months ahead), at high resolution, and across a large spatial scale, including in extreme drought conditions. D‐SDM predictive accuracy and near‐term hindcast reliability were primarily driven by the availability of training data rather than overarching weather conditions. We discuss how a forecasting system could be used to inform adaptive management of mobile species and mitigate impacts of extreme weather, including by anticipating sites and times for transient management and proactively mobilising resources for prepared responses. Our results suggest that such techniques could be widely applied to inform more resilient, adaptive management of mobile species worldwide.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Mutagenesis on a complex mouse genetic background by site-specific nucleases - Benjamin Davies; Lucy Trelfa; Victoria S. Rashbrook; Edward Drydale; Rachel Martin; Boyan Bai; Jedrzej Golebka; Daniel Stephen Biggs; Keith M. Channon; Shoumo Bhattacharya; Gillian Douglas (Transgenic Research, 2024)
Mouse models with complex genetic backgrounds are increasingly used in preclinical research to accurately model human disease and to enable temporal and cell-specific evaluation of genetic manipulations. Backcrossing mice onto these complex genetic backgrounds takes time and leads to significant wastage of animals. In this study, we aimed to evaluate whether site-specific nucleases could be used to generate additional genetic mutations in a complex genetic background, using the REVERSA mouse model of atherosclerosis, a model harbouring four genetically altered alleles. The model is comprised of a functional null mutation in the Ldlr gene in combination with a ApoB100 allele, which, after high-fat diet, leads to the rapid development of atherosclerosis. The regression of the pathology is achieved by inducible knock-out of the Mttp gene. Here we report an investigation to establish if microinjection of site-specific nucleases directly into zygotes prepared from the REVERSA could be used to investigate the role of the ATP binding cassette transporter G1 (ABCG1) in atherosclerosis regression. We show that using this approach we could successfully generate two independent knockout lines on the REVERSA background, both of which exhibited the expected phenotype of a significant reduction in cholesterol efflux to HDL in bone marrow-derived macrophages. However, loss of Abcg1 did not impact atherosclerosis regression in either the aortic root or in aortic arch, demonstrating no important role for this transporter subtype. We have demonstrated that site-specific nucleases can be used to create genetic modifications directly onto complex disease backgrounds and can be used to explore gene function without the need for laborious backcrossing of independent strains, conveying a significant 3Rs advantage.

Exposure of satellite tagged bowhead whales ( Balaena mysticetus ) to transiting vessels in the Eastern Canadian Arctic - Morgan J. Martin; William D. Halliday; Steven H. Ferguson; Brent G. Young; Rachel Charish; Jackie Dawson; Sarah M. E. Fortune; Francis Juanes; Levi Qaunaq; Stephen J. Insley (Marine Mammal Science, 2024)
Climate change poses new challenges to Arctic marine mammals, with increasing vessel traffic and associated underwater noise pollution emerging as significant threats. The bowhead whale ( Balaena mysticetus ), an endemic Arctic cetacean, faces these new threats. The Eastern Canada‐West Greenland (ECWG) bowhead whale population migrates through areas with the highest levels of vessel traffic in the Canadian Arctic. Here, we document the spatial and temporal overlap between 36 satellite‐tagged ECWG bowhead whales and vessels equipped with Automatic Identification System (AIS) transponders during 2012–2017. We report 1,145 instances where vessels were within 125 km of a tagged whale, with 306 occurrences within distances ≤50 km. Overlap between vessels and tagged bowhead whales was quantified monthly within years to investigate individual whale encounter rates. Results indicate that ECWG bowhead whales encounter the majority (79%) of vessels annually during August–October, with the highest number of encounters (42%) observed in September. Encounter rates ranged from 0.25 to 0.51 vessels encountered per day per whale during August–October compared to

The need for guidance in antidepressant drug development: Revisiting the role of the forced swim test and tail suspension test - Emily R. Trunnell; Julia Baines; Stephen Farghali; Tara Jackson; Kimberley Jayne; Rachel Smith; Tina Stibbe (Regulatory Toxicology and Pharmacology, 2024)

The National Wastewater Surveillance System (NWSS): From inception to widespread coverage, 2020–2022, United States - Carly Adams; Megan Bias; Rory M. Welsh; Jenna Webb; Heather Reese; Stephen Delgado; John Person; Rachel West; Soo Shin; Amy Kirby (Science of The Total Environment, 2024)

Apomixis goes a long way: Genetic evidence of persistence and long‐distance seed dispersal in an ancient landscape - Nicola Delnevo; Rachel M. Binks; Stephen van Leeuwen; David J. Coates; Shelley McArthur; Bronwyn M. Macdonald; Margaret Hankinson; Margaret Byrne (Journal of Biogeography, 2024)
Aim Apomixis is a widespread trait in extreme environments worldwide, yet phylogeographical studies for species exhibiting these complex reproductive systems are still limited to temperate zones in the Northern Hemisphere. Through analyses of a combination of adult plants and seedlings, and nuclear and chloroplast DNA, we assessed the contemporary genetic outcomes of apomixis and phylogeographical patterns in an arid unglaciated landscape to understand the evolutionary trajectory of apomictic species. Location Pilbara bioregion, north‐western Australia. Taxon Senna glutinosa subsp. glutinosa . Materials and Methods Spatial patterns of genetic diversity and differentiation in three chloroplast regions and 17 nuclear microsatellite markers were evaluated in 480 plants from 20 populations of S. glutinosa subsp. glutinosa across the Pilbara bioregion. We also germinated and genotyped seed for a progeny analysis to quantify polyembryony and the relative frequency of asexual versus sexual reproduction. Results We found frequent polyembryony and a high proportion of asexual offspring (84.56%), resulting in low within‐population genotypic diversity. The nuclear dataset identified 72 multilocus lineages (MLLs) with moderate pairwise population genetic fixation and low differentiation among populations with no geographically structured genetic clustering. Chloroplast DNA showed high haplotype diversity and a widespread distribution of haplotypes. Only one peripheral population presented a single unique haplotype and MLL. Main Conclusions Analysis of this woody perennial in an arid landscape shows the influence of apomixis on genetic patterns and species persistence. Haplotype diversity was indicative of long‐term persistence within the ancient Pilbara region. Widespread distribution of haplotypes and sharing of several nuclear MLLs among distant populations indicated extensive seed dispersal throughout the study area. The combination of polyploidy, facultative apomixis and extensive seed dispersal maintains genetic variability within local populations and promotes the spread of advantageous genotypes across wide geographical distances. Therefore, apomixis, rather than an evolutionary ‘dead‐end’, can be regarded as a mechanism facilitating evolutionary success of apomictic species in extreme and complex environments.

Wind erosion and transport on planetesimals - Alice C. Quillen; Stephen Luniewski; Adam E. Rubinstein; Jérémy Couturier; Rachel Glade; Miki Nakajima (Icarus, 2024)

Microbes, the ‘silent third partners’ of bee–angiosperm mutualisms - Shawn A. Steffan; Prarthana S. Dharampal; Jordan G. Kueneman; Alexander Keller; Magda P. Argueta-Guzmán; Quinn S. McFrederick; Stephen L. Buchmann; Rachel L. Vannette; Anna F. Edlund; Celeste C. Mezera; Nolan Amon; Bryan N. Danforth (Trends in Ecology & Evolution, 2024)

Phospholipid chlorohydrins as chlorine exposure biomarkers in a large animal model - Petrus Hemström; Bronwen Jugg; Rachel Watkins; Sofia Jonasson; Linda Elfsmark; Stephen Rutter; Crister Åstot; Pernilla Lindén (Toxicology Letters, 2024)

Anoxia begets anoxia: A positive feedback to the deoxygenation of temperate lakes - Abigail S. L. Lewis; Maximilian P. Lau; Stephen F. Jane; Kevin C. Rose; Yaron Be'eri‐Shlevin; Sarah H. Burnet; François Clayer; Heidrun Feuchtmayr; Hans‐Peter Grossart; Dexter W. Howard; Heather Mariash; Jordi Delgado Martin; et al. (Global Change Biology, 2024)
Declining oxygen concentrations in the deep waters of lakes worldwide pose a pressing environmental and societal challenge. Existing theory suggests that low deep‐water dissolved oxygen (DO) concentrations could trigger a positive feedback through which anoxia (i.e., very low DO) during a given summer begets increasingly severe occurrences of anoxia in following summers. Specifically, anoxic conditions can promote nutrient release from sediments, thereby stimulating phytoplankton growth, and subsequent phytoplankton decomposition can fuel heterotrophic respiration, resulting in increased spatial extent and duration of anoxia. However, while the individual relationships in this feedback are well established, to our knowledge, there has not been a systematic analysis within or across lakes that simultaneously demonstrates all of the mechanisms necessary to produce a positive feedback that reinforces anoxia. Here, we compiled data from 656 widespread temperate lakes and reservoirs to analyze the proposed anoxia begets anoxia feedback. Lakes in the dataset span a broad range of surface area (1–126,909 ha), maximum depth (6–370 m), and morphometry, with a median time‐series duration of 30 years at each lake. Using linear mixed models, we found support for each of the positive feedback relationships between anoxia, phosphorus concentrations, chlorophyll a concentrations, and oxygen demand across the 656‐lake dataset. Likewise, we found further support for these relationships by analyzing time‐series data from individual lakes. Our results indicate that the strength of these feedback relationships may vary with lake‐specific characteristics: For example, we found that surface phosphorus concentrations were more positively associated with chlorophyll a in high‐phosphorus lakes, and oxygen demand had a stronger influence on the extent of anoxia in deep lakes. Taken together, these results support the existence of a positive feedback that could magnify the effects of climate change and other anthropogenic pressures driving the development of anoxia in lakes around the world.

Are transport networks in low-income countries prepared for climate change? Barriers to preparing for climate change in Africa and South Asia - Sarah Greenham; Robin Workman; Kevin McPherson; Emma Ferranti; Rachel Fisher; Stephen Mills; Roger Street; John Dora; Andrew Quinn; Clive Roberts (Mitigation and Adaptation Strategies for Global Change, 2023)
Climate change, through extreme weather events and slow onset climatic changes, disrupts the operation of transport networks, and those in low-income countries (LICs) across Africa and South Asia are particularly vulnerable to climate change. This paper explores the barriers that LICs face across Africa and South Asia regarding preparedness of transport infrastructure to climate change, with the intent of addressing the knowledge gaps and consequential needs of LICs to support the delivery of more climate-resilient transport. Literature on climate change adaptation and transport resilience among LICs is reviewed to identify the broad challenges and barriers regarding climate change adaptation. Semi-structured interviews with 13 transport stakeholders across Africa and South Asia were also conducted to understand the challenges specific to the transport sector in the regions. Several barriers were identified, including a lack of data and knowledge on climate change impacts, design and prioritisation of remedial actions, budgeting and planning for climate change, and identifying and engaging with stakeholders. Findings from this paper and the wider research project it comprises inform policy guidance that calls for greater national and international coordination to develop practical, relevant and usable data, tools, advice and support for some of the most at-risk transport networks to climate change in the world.

Seasonal community dynamics and toxicity potential of cyanobacteria in Lough Arrow, an oligo-mesotrophic lake in the north-west of Ireland - Darren Garland; Henry Koehler; Stephen McGirr; Rachel Parkes; Frances E Lucy; Nicolas Touzet (Limnologica, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The influence of complex matrices on method performance in extracting and monitoring for microplastics - Leah M. Thornton Hampton; Hannah De Frond; Kristine Gesulga; Syd Kotar; Wenjian Lao; Cindy Matuch; Stephen B. Weisberg; Charles S. Wong; Susanne Brander; Silke Christansen; Cayla R. Cook; Fangni Du; et al. (Chemosphere, 2023)

The spontaneous mouse mutant low set ears (Lse) is caused by tandem duplication of Fgf3 and Fgf4 - Alana Luzzio; Sarah Edie; Kristina Palmer; L. Brianna Caddle; Rachel Urban; Leslie O. Goodwin; Ian C. Welsh; Laura G. Reinholdt; David E. Bergstrom; Timothy C. Cox; Leah Rae Donahue; Stephen A. Murray (Mammalian Genome, 2023)

Sex-specific respiratory and systemic endocrine effects of acute acrolein and trichloroethylene inhalation - Devin I. Alewel; Thomas W. Jackson; Samuel A. Vance; Mette C. Schladweiler; Paul A. Evansky; Andres R. Henriquez; Rachel Grindstaff; Stephen H. Gavett; Urmila P. Kodavanti (Toxicology Letters, 2023)

Transcriptomic Profiling Reveals Discrete Poststroke Dementia Neuronal and Gliovascular Signatures - Rachel Waller; Yoshiki Hase; Julie E. Simpson; Paul R. Heath; Matthew Wyles; Rajesh N. Kalaria; Stephen B. Wharton (Translational Stroke Research, 2023)
Poststroke dementia (PSD) is associated with pathology in frontal brain regions, in particular dorsolateral prefrontal cortex (DLPFC) neurons and white matter, remote from the infarct. We hypothesised that PSD results from progressive DLPFC neuronal damage, associated with frontal white matter gliovascular unit (GVU) alterations. We investigated the transcriptomic profile of the neurons and white matter GVU cells previously implicated in pathology. Laser-capture microdissected neurons, astrocytes and endothelial cells were obtained from the Cognitive Function After Stroke cohort of control, PSD and poststroke non-dementia (PSND) human subjects. Gene expression was assessed using microarrays and pathway analysis to compare changes in PSD with controls and PSND. Neuronal findings were validated using NanoString technology and compared with those in the bilateral common carotid artery stenosis (BCAS) mouse model. Comparing changes in PSD compared to controls with changes in PSND compared to controls identified transcriptomic changes associated specifically with dementia. DLPFC neurons showed defects in energy production (tricarboxylic acid (TCA) cycle, adenosine triphosphate (ATP) binding and mitochondria), signalling and communication (MAPK signalling, Toll-like receptor signalling, endocytosis). Similar changes were identified in neurons isolated from BCAS mice. Neuronal findings accompanied by altered astrocyte communication and endothelium immune changes in the frontal white matter, suggesting GVU dysfunction. We propose a pathogenic model in PSD whereby neuronal changes are associated with frontal white matter GVU dysfunction leading to astrocyte failure in supporting neuronal circuits resulting in delayed cognitive decline associated with PSD. Therefore, targeting these processes could potentially ameliorate the dementia seen in PSD.

Correction: Reading the biomineralized book of life: expanding otolith biogeochemical research and applications for fisheries and ecosystem-based management - Patrick Reis-Santos; Bronwyn M. Gillanders; Anna M. Sturrock; Christopher Izzo; Dion S. Oxman; Jessica A. Lueders-Dumont; Karin Hüssy; Susanne E. Tanner; Troy Rogers; Zoë A. Doubleday; Allen H. Andrews; Clive Trueman; et al. (Reviews in Fish Biology and Fisheries, 2023)

Reading the biomineralized book of life: expanding otolith biogeochemical research and applications for fisheries and ecosystem-based management - Patrick Reis-Santos; Bronwyn M. Gillanders; Anna M. Sturrock; Christopher Izzo; Dion S. Oxman; Jessica A. Lueders-Dumont; Karin Hüssy; Susanne E. Tanner; Troy Rogers; Zoë A. Doubleday; Allen H. Andrews; Clive Trueman; et al. (Reviews in Fish Biology and Fisheries, 2023)
Chemical analysis of calcified structures continues to flourish, as analytical and technological advances enable researchers to tap into trace elements and isotopes taken up in otoliths and other archival tissues at ever greater resolution. Increasingly, these tracers are applied to refine age estimation and interpretation, and to chronicle responses to environmental stressors, linking these to ecological, physiological, and life-history processes. Here, we review emerging approaches and innovative research directions in otolith chemistry, as well as in the chemistry of other archival tissues, outlining their value for fisheries and ecosystem-based management, turning the spotlight on areas where such biomarkers can support decision making. We summarise recent milestones and the challenges that lie ahead to using otoliths and archival tissues as biomarkers, grouped into seven, rapidly expanding and application-oriented research areas that apply chemical analysis in a variety of contexts, namely: (1) supporting fish age estimation; (2) evaluating environmental stress, ecophysiology and individual performance; (3) confirming seafood provenance; (4) resolving connectivity and movement pathways; (5) characterising food webs and trophic interactions; (6) reconstructing reproductive life histories; and (7) tracing stock enhancement efforts. Emerging research directions that apply hard part chemistry to combat seafood fraud, quantify past food webs, as well as to reconcile growth, movement, thermal, metabolic, stress and reproductive life-histories provide opportunities to examine how harvesting and global change impact fish health and fisheries productivity. Ultimately, improved appreciation of the many practical benefits of archival tissue chemistry to fisheries and ecosystem-based management will support their increased implementation into routine monitoring. Graphical abstract

Uranus ring occultation observations: 1977–2006 - Richard G. French; Colleen A. McGhee-French; Mitchell Gordon; Richard L. Baron; Amanda S. Bosh; Marc W. Buie; Nancy Chanover; Mary Ann Clark; Edward W. Dunham; Linda M. French; Ian S. Glass; Jay D. Goguen; et al. (Icarus, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

The protist community traces seasonality and mesoscale hydrographic features in the oligotrophic Sargasso Sea - Leocadio Blanco-Bercial; Rachel Parsons; Luis M. Bolaños; Rod Johnson; Stephen J. Giovannoni; Ruth Curry (Frontiers in Marine Science, 2022)
Protists represent the majority of the eukaryotic diversity in the oceans. They have different functions in the marine food web, playing essential roles in the biogeochemical cycles. While the available data is rich in horizontal and temporal coverage, little is known on their vertical structuring, particularly below the photic zone. The present study applies V4 18S rDNA metabarcoding to samples collected over three years in conjunction with the BATS time-series to assess marine protist communities in the epipelagic and mesopelagic zones (0-1000 m). The protist community showed a dynamic seasonality in the epipelagic, responding to hydrographic yearly cycles. Mixotrophic lineages dominated throughout the year. However, autotrophs bloomed during the rapid transition between the winter mixing and the stratified summer, and heterotrophs had their peak at the end of summer, when the base of the thermocline reaches its deepest depth. Below the photic zone, the community, dominated by Rhizaria, is depth-stratified and relatively constant throughout the year, although they followed local hydrographic and biological features such as the oxygen minimum zone. The results suggest a dynamic partitioning of the water column, where the niche vertical position for each community changes throughout the year in the epipelagic, likely depending on nutrient availability, the mixed layer depth, and other hydrographic features. At depth, the protist community closely tracked mesoscale events (eddies), where the communities followed the hydrographic uplift, raising the deeper communities for hundreds of meters, and compressing the communities above.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The clinical features of polymerase proof-reading associated polyposis (PPAP) and recommendations for patient management - Claire Palles; Lynn Martin; Enric Domingo; Laura Chegwidden; Josh McGuire; Vicky Cuthill; Ellen Heitzer; Rachel Kerr; David Kerr; Stephen Kearsey; Susan K. Clark; Ian Tomlinson; et al. (Familial Cancer, 2022)
Pathogenic germline exonuclease domain (ED) variants of POLE and POLD1 cause the Mendelian dominant condition polymerase proof-reading associated polyposis (PPAP). We aimed to describe the clinical features of all PPAP patients with probably pathogenic variants. We identified patients with a variants mapping to the EDs of POLE or POLD1 from cancer genetics clinics, a colorectal cancer (CRC) clinical trial, and systematic review of the literature. We used multiple evidence sources to separate ED variants into those with strong evidence of pathogenicity and those of uncertain importance. We performed quantitative analysis of the risk of CRC, colorectal adenomas, endometrial cancer or any cancer in the former group. 132 individuals carried a probably pathogenic ED variant (105 POLE , 27 POLD1 ). The earliest malignancy was colorectal cancer at 14. The most common tumour types were colorectal, followed by endometrial in POLD1 heterozygotes and duodenal in POLE heterozygotes. POLD1- mutant cases were at a significantly higher risk of endometrial cancer than POLE heterozygotes. Five individuals with a POLE pathogenic variant, but none with a POLD1 pathogenic variant, developed ovarian cancer. Nine patients with POLE pathogenic variants and one with a POLD1 pathogenic variant developed brain tumours. Our data provide important evidence for PPAP management. Colonoscopic surveillance is recommended from age 14 and upper-gastrointestinal surveillance from age 25. The management of other tumour risks remains uncertain, but surveillance should be considered. In the absence of strong genotype–phenotype associations, these recommendations should apply to all PPAP patients.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Climate policy conflict in the U.S. states: a critical review and way forward - Joshua A. Basseches; Rebecca Bromley-Trujillo; Maxwell T. Boykoff; Trevor Culhane; Galen Hall; Noel Healy; David J. Hess; David Hsu; Rachel M. Krause; Harland Prechel; J. Timmons Roberts; Jennie C. Stephens (Climatic Change, 2022)
Many U.S. states have taken significant action on climate change in recent years, demonstrating their commitment despite federal policy gridlock and rollbacks. Yet, there is still much we do not know about the agents, discourses, and strategies of those seeking to delay or obstruct state-level climate action. We first ask, what are the obstacles to strong and effective climate policy within U.S. states? We review the political structures and interest groups that slow action, and we examine emerging tensions between climate justice and the technocratic and/or market-oriented approaches traditionally taken by many mainstream environmental groups. Second, what are potential solutions for overcoming these obstacles? We suggest strategies for overcoming opposition to climate action that may advance more effective and inclusive state policy, focusing on political strategies, media framing, collaboration, and leveraging the efforts of ambitious local governments.

Shifting baselines and cross‐scale drivers of lake water clarity: Applications for lake assessment - Jeremy Deeds; Aria Amirbahman; Stephen A. Norton; Linda C. Bacon; Rachel A. Hovel (Limnology and Oceanography, 2022)
Temporal Secchi depth trends are used in lake assessment to evaluate lake condition and possible shifts in trophic state. For accurate lake assessments, it is important to differentiate regional trends from lake‐specific trends, but this can be confounded by interacting factors. We present a divergent trend analysis which uses temporal patterns of Secchi depth water clarity from 1999 to 2018 for five different types of reference lakes from minimally disturbed watersheds to create dynamic baselines against which we evaluate Secchi depth trends from nonreference lakes in Maine, USA. We used mixed‐effect generalized additive models to generate smoothed curves of the expected baseline Secchi depth for each reference lake type to account for the nonlinear dynamics of lake condition through time. The majority of nonreference lakes (74%) showed no difference between measured trend (actual Secchi depth data) and divergent trend (residual Secchi depth from baseline trends). The most common difference in lakes with inconsistent trend test results showed stability in measured trends but apparent declining trends in divergent Secchi depth clarity. We used a Dynamic Factor Analysis (DFA) model to help interpret the variation and shifts observed in baseline reference lake trends. The best DFA model identified two common trends in water clarity among lake types and precipitation during the primary stratification season as the most informative covariable. Because precipitation amount and intensity are expected to increase according to predictive climate models for the Northeast US, our results suggest that baseline lake clarity in Maine will decrease with climate change.

Mean-Field Models for EEG/MEG: From Oscillations to Waves - Áine Byrne; James Ross; Rachel Nicks; Stephen Coombes (Brain Topography, 2022)
Neural mass models have been used since the 1970s to model the coarse-grained activity of large populations of neurons. They have proven especially fruitful for understanding brain rhythms. However, although motivated by neurobiological considerations they are phenomenological in nature, and cannot hope to recreate some of the rich repertoire of responses seen in real neuronal tissue. Here we consider a simple spiking neuron network model that has recently been shown to admit an exact mean-field description for both synaptic and gap-junction interactions. The mean-field model takes a similar form to a standard neural mass model, with an additional dynamical equation to describe the evolution of within-population synchrony. As well as reviewing the origins of this next generation mass model we discuss its extension to describe an idealised spatially extended planar cortex. To emphasise the usefulness of this model for EEG/MEG modelling we show how it can be used to uncover the role of local gap-junction coupling in shaping large scale synaptic waves.

Comparison of benthic macroinvertebrate assessment methods along a salinity gradient in headwater streams - Rachel A. Pence; Thomas R. Cianciolo; Damion R. Drover; Daniel L. McLaughlin; David J. Soucek; Anthony J. Timpano; Carl E. Zipper; Stephen H. Schoenholtz (Environmental Monitoring and Assessment, 2021)

Correction to: Notch regulates vascular collagen IV basement membrane through modulation of lysyl hydroxylase 3 trafficking - Stephen J. Gross; Amelia M. Webb; Alek D. Peterlin; Jessica R. Durrant; Rachel J. Judson; Qanber Raza; Jan K. Kitajewski; Erich J. Kushner (Angiogenesis, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s10456-021-09801-w

Notch regulates vascular collagen IV basement membrane through modulation of lysyl hydroxylase 3 trafficking - Stephen J. Gross; Amelia M. Webb; Alek D. Peterlin; Jessica R. Durrant; Rachel J. Judson; Qanber Raza; Jan K. Kitajewski; Erich J. Kushner (Angiogenesis, 2021)
Collagen type IV (Col IV) is a basement membrane protein associated with early blood vessel morphogenesis and is essential for blood vessel stability. Defects in vascular Col IV deposition are the basis of heritable disorders, such as small vessel disease, marked by cerebral hemorrhage and drastically shorten lifespan. To date, little is known about how endothelial cells regulate the intracellular transport and selective secretion of Col IV in response to angiogenic cues, leaving a void in our understanding of this critical process. Our aim was to identify trafficking pathways that regulate Col IV deposition during angiogenic blood vessel development. We have identified the GTPase Rab10 as a major regulator of Col IV vesicular trafficking during vascular development using both in vitro imaging and biochemistry as well as in vivo models. Knockdown of Rab10 reduced de novo Col IV secretion in vivo and in vitro. Mechanistically, we determined that Rab10 is an indirect mediator of Col IV secretion, partnering with atypical Rab25 to deliver the enzyme lysyl hydroxylase 3 (LH3) to Col IV-containing vesicles staged for secretion. Loss of Rab10 or Rab25 results in depletion of LH3 from Col IV-containing vesicles and rapid lysosomal degradation of Col IV. Furthermore, we demonstrate that Rab10 is Notch responsive, indicating a novel connection between permissive Notch-based vessel maturation programs and vesicle trafficking. Our results illustrate both a new trafficking-based component in the regulated secretion of Col IV and how this vesicle trafficking program interfaces with Notch signaling to fine-tune basement membrane secretion during blood vessel development.

The success of the Montreal Protocol in mitigating interactive effects of stratospheric ozone depletion and climate change on the environment - Paul W. Barnes; Janet F. Bornman; Krishna K. Pandey; Germar H. Bernhard; Alkiviadis F. Bais; Rachel E. Neale; Thomas Matthew Robson; Patrick J. Neale; Craig E. Williamson; Richard G. Zepp; Sasha Madronich; Stephen R. Wilson; et al. (Global Change Biology, 2021)

Divergent climate change effects on widespread dryland plant communities driven by climatic and ecohydrological gradients - Kyle A. Palmquist; Daniel R. Schlaepfer; Rachel R. Renne; Stephen C. Torbit; Kevin E. Doherty; Thomas E. Remington; Greg Watson; John B. Bradford; William K. Lauenroth (Global Change Biology, 2021)
Plant community response to climate change will be influenced by individual plant responses that emerge from competition for limiting resources that fluctuate through time and vary across space. Projecting these responses requires an approach that integrates environmental conditions and species interactions that result from future climatic variability. Dryland plant communities are being substantially affected by climate change because their structure and function are closely tied to precipitation and temperature, yet impacts vary substantially due to environmental heterogeneity, especially in topographically complex regions. Here, we quantified the effects of climate change on big sagebrush ( Artemisia tridentata Nutt.) plant communities that span 76 million ha in the western United States. We used an individual‐based plant simulation model that represents intra‐ and inter‐specific competition for water availability, which is represented by a process‐based soil water balance model. For dominant plant functional types, we quantified changes in biomass and characterized agreement among 52 future climate scenarios. We then used a multivariate matching algorithm to generate fine‐scale interpolated surfaces of functional type biomass for our study area. Results suggest geographically divergent responses of big sagebrush to climate change (changes in biomass of −20% to +27%), declines in perennial C 3 grass and perennial forb biomass in most sites, and widespread, consistent, and sometimes large increases in perennial C 4 grasses. The largest declines in big sagebrush, perennial C 3 grass and perennial forb biomass were simulated in warm, dry sites. In contrast, we simulated no change or increases in functional type biomass in cold, moist sites. There was high agreement among climate scenarios on climate change impacts to functional type biomass, except for big sagebrush. Collectively, these results suggest divergent responses to warming in moisture‐limited versus temperature‐limited sites and potential shifts in the relative importance of some of the dominant functional types that result from competition for limiting resources.

Montane Meadows: A Soil Carbon Sink or Source? - Cody C. Reed; Amy G. Merrill; W. Mark Drew; Beth Christman; Rachel A. Hutchinson; Levi Keszey; Melissa Odell; Sherman Swanson; Paul S. J. Verburg; Jim Wilcox; Stephen C. Hart; Benjamin W. Sullivan (Ecosystems, 2021)

Timing and pace of ice‐sheet withdrawal across the marine–terrestrial transition west of Ireland during the last glaciation - Colm Ó Cofaigh; S. Louise Callard; David H. Roberts; Richard C. Chiverrell; C. K. Ballantyne; David J. A. Evans; Margot Saher; Katrien J. J. Van Landeghem; Rachel Smedley; Sara Benetti; Matthew Burke; Chris D. Clark; et al. (Journal of Quaternary Science, 2021)
Understanding the pace and drivers of marine‐based ice‐sheet retreat relies upon the integration of numerical ice‐sheet models with observations from contemporary polar ice sheets and well‐constrained palaeo‐glaciological reconstructions. This paper provides a reconstruction of the retreat of the last British–Irish Ice Sheet (BIIS) from the Atlantic shelf west of Ireland during and following the Last Glacial Maximum (LGM). It uses marine‐geophysical data and sediment cores dated by radiocarbon, combined with terrestrial cosmogenic nuclide and optically stimulated luminescence dating of onshore ice‐marginal landforms, to reconstruct the timing and rate of ice‐sheet retreat from the continental shelf and across the adjoining coastline of Ireland, thus including the switch from a marine‐ to a terrestrially‐based ice‐sheet margin. Seafloor bathymetric data in the form of moraines and grounding‐zone wedges on the continental shelf record an extensive ice sheet west of Ireland during the LGM which advanced to the outer shelf. This interpretation is supported by the presence of dated subglacial tills and overridden glacimarine sediments from across the Porcupine Bank, a westwards extension of the Irish continental shelf. The ice sheet was grounded on the outer shelf at ~26.8 ka cal bp with initial retreat underway by 25.9 ka cal bp. Retreat was not a continuous process but was punctuated by marginal oscillations until ~24.3 ka cal bp. The ice sheet thereafter retreated to the mid‐shelf where it formed a large grounding‐zone complex at ~23.7 ka cal bp. This retreat occurred in a glacimarine environment. The Aran Islands on the inner continental shelf were ice‐free by ~19.5 ka bp and the ice sheet had become largely terrestrially based by 17.3 ka bp. This suggests that the Aran Islands acted to stabilize and slow overall ice‐sheet retreat once the BIIS margin had reached the inner shelf. Our results constrain the timing of initial retreat of the BIIS from the outer shelf west of Ireland to the period of minimum global eustatic sea level. Initial retreat was driven, at least in part, by glacio‐isostatically induced, high relative sea level. Net rates of ice‐sheet retreat across the shelf were slow (62–19 m a −1 ) and reduced (8 m a −1 ) as the ice sheet vacated the inner shelf and moved onshore. A picture therefore emerges of an extensive BIIS on the Atlantic shelf west of Ireland, in which early, oscillatory retreat was followed by slow episodic retreat which decelerated further as the ice margin became terrestrially based. More broadly, this demonstrates the importance of localized controls, in particular bed topography, on modulating the retreat of marine‐based sectors of ice sheets.

The evolution of the terrestrial‐terminating Irish Sea glacier during the last glaciation - Richard Christopher Chiverrell; Geoff Stephen Powell Thomas; Matthew Burke; Alicia Medialdea; Rachel Smedley; Mark Bateman; Chris Clark; Geoffrey A. T. Duller; Derek Fabel; Geraint Jenkins; Xianjiao Ou; Helen Marie Roberts; et al. (Journal of Quaternary Science, 2021)
Here we reconstruct the last advance to maximum limits and retreat of the Irish Sea Glacier (ISG), the only land‐terminating ice lobe of the western British Irish Ice Sheet. A series of reverse bedrock slopes rendered proglacial lakes endemic, forming time‐transgressive moraine‐ and bedrock‐dammed basins that evolved with ice marginal retreat. Combining, for the first time on glacial sediments, optically stimulated luminescence (OSL) bleaching profiles for cobbles with single grain and small aliquot OSL measurements on sands, has produced a coherent chronology from these heterogeneously bleached samples. This chronology constrains what is globally an early build‐up of ice during late Marine Isotope Stage 3 and Greenland Stadial (GS) 5, with ice margins reaching south Lancashire by 30 ± 1.2 ka, followed by a 120‐km advance at 28.3 ± 1.4 ka reaching its 26.5 ± 1.1 ka maximum extent during GS‐3. Early retreat during GS‐3 reflects piracy of ice sources shared with the Irish‐Sea Ice Stream (ISIS), starving the ISG. With ISG retreat, an opportunistic readvance of Welsh ice during GS‐2 rode over the ISG moraines occupying the space vacated, with ice margins oscillating within a substantial glacial over‐deepening. Our geomorphological chronosequence shows a glacial system forced by climate but mediated by piracy of ice sources shared with the ISIS, changing flow regimes and fronting environments.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Influence of Rocky Shore Characteristics on the Foraging Profitability of Eurasian Oystercatchers Haematopus ostralegus - Rachel Edwards; Lucy Rossiter; Rajarathinavelu Nagarajan; Stephen E. G. Lea (Wetlands, 2021)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Different carboxyl‐rich alicyclic molecules proxy compounds select distinct bacterioplankton for oxidation of dissolved organic matter in the mesopelagic Sargasso Sea - Shuting Liu; Rachel Parsons; Keri Opalk; Nicholas Baetge; Stephen Giovannoni; Luis M. Bolaños; Elizabeth B. Kujawinski; Krista Longnecker; YueHan Lu; Elisa Halewood; Craig A. Carlson (Limnology and Oceanography, 2020)
Marine dissolved organic matter (DOM) varies in its recalcitrance to rapid microbial degradation. DOM of varying recalcitrance can be exported from the ocean surface to depth by subduction or convective mixing and oxidized over months to decades in deeper seawater. Carboxyl‐rich alicyclic molecules (CRAM) are characterized as a major component of recalcitrant DOM throughout the oceanic water column. The oxidation of CRAM‐like compounds may depend on specific bacterioplankton lineages with oxidative enzymes capable of catabolizing complex molecular structures like long‐chain aliphatics, cyclic alkanes, and carboxylic acids. To investigate the interaction between bacteria and CRAM‐like compounds, we conducted microbial remineralization experiments using several compounds rich in carboxyl groups and/or alicyclic rings, including deoxycholate, humic acid, lignin, and benzoic acid, as proxies for CRAM. Mesopelagic seawater (200 m) from the northwest Sargasso Sea was used as media and inoculum and incubated over 28 d. All amendments demonstrated significant DOC removal (2–11 μ mol C L −1 ) compared to controls. Bacterioplankton abundance increased significantly in the deoxycholate and benzoic acid treatments relative to controls, with fast‐growing Spongiibacteracea , Euryarcheaota, and slow‐growing SAR11 enriched in the deoxycholate treatment and fast‐growing Alteromonas , Euryarcheaota, and Thaumarcheaota enriched in the benzoic acid treatment. In contrast, bacterioplankton grew slower in the lignin and humic acid treatments, with oligotrophic SAR202 becoming significantly enriched in the lignin treatment. Our results indicate that the character of the CRAM proxy compounds resulted in distinct bacterioplankton removal rates of DOM and affected specific lineages of bacterioplankton capable of responding.

Beyond Technical Fixes: climate solutions and the great derangement - Andrea Joslyn Nightingale; Siri Eriksen; Marcus Taylor; Timothy Forsyth; Mark Pelling; Andrew Newsham; Emily Boyd; Katrina Brown; Blane Harvey; Lindsey Jones; Rachel Bezner Kerr; Lyla Mehta; et al. (Climate and Development, 2020)

Endosymbiont diversity and community structure in Porites lutea from Southeast Asia are driven by a suite of environmental variables - Yuen Ting Rachel Tan; Benjamin J. Wainwright; Lutfi Afiq-Rosli; Yin Cheong Aden Ip; Jen Nie Lee; Nhung Thi Hong Nguyen; Stephen B. Pointing; Danwei Huang (Symbiosis, 2020)
Many corals depend upon the highly specialised and intricate relationship they form with Symbiodiniaceae algal symbionts. Porites lutea is a massive reef-building coral found throughout Southeast Asia that hosts these endosymbionts obligately. Yet despite the prevalence and importance of P. lutea as one of the most dominant corals here, its associated Symbiodiniaceae communities have not been precisely characterised. In this study, we used high-throughput DNA amplicon sequencing of the nuclear internal transcribed spacer 2 (ITS2) to characterise the diversity, community structure and biogeographic distribution of Symbiodiniaceae in P. lutea throughout Singapore and Peninsular Malaysia. Consistent with previous studies, we found that Cladocopium was the most dominant genus among all samples, and Cladocopium C15 was the most dominant type (or subclade) with 100% occurrence in all samples from every study site. Results also revealed numerous Symbiodiniaceae types associated with P. lutea that were previously undetected in Southeast Asia. Endosymbiont diversity and community variation are driven by a combination of site-specific mean monthly cloud cover and variance in monthly sea surface temperature. This study contributes baseline data toward understanding differences in Symbiodiniaceae assemblages hosted by P. lutea , shedding light on how they might be indicative of particular environmental conditions and coral responses.

Population genetics of fruit bat reservoir informs the dynamics, distribution and diversity of Nipah virus - Kevin J. Olival; Alice Latinne; Ariful Islam; Jonathan H. Epstein; Rebecca Hersch; Rachel C. Engstrand; Emily S. Gurley; George Amato; Stephen P. Luby; Peter Daszak (Molecular Ecology, 2020)
The structure and connectivity of wildlife host populations may influence zoonotic disease dynamics, evolution and therefore spillover risk to people. Fruit bats in the genus Pteropus , or flying foxes, are the primary natural reservoir for henipaviruses—a group of emerging paramyxoviruses that threaten livestock and public health. In Bangladesh, Pteropus medius is the reservoir for Nipah virus—and viral spillover has led to human fatalities nearly every year since 2001. Here, we use mitochondrial DNA and nuclear microsatellite markers to measure the population structure, demographic history and phylogeography of P. medius in Bangladesh. We combine this with a phylogeographic analysis of all known Nipah virus sequences and strains currently available to better inform the dynamics, distribution and evolutionary history of Nipah virus. We show that P. medius is primarily panmictic, but combined analysis of microsatellite and morphological data shows evidence for differentiation of two populations in eastern Bangladesh, corresponding to a divergent strain of Nipah virus also found in bats from eastern Bangladesh. Our demographic analyses indicate that a large, expanding population of flying foxes has existed in Bangladesh since the Late Pleistocene, coinciding with human population expansion in South Asia, suggesting repeated historical spillover of Nipah virus likely occurred. We present the first evidence of mitochondrial introgression, or hybridization, between P. medius and flying fox species found in South‐East Asia ( P. vampyrus and P. hypomelanus ), which may help to explain the distribution of Nipah virus strains across the region.

State of the science in reconciling top‐down and bottom‐up approaches for terrestrial CO 2 budget - Masayuki Kondo; Prabir K. Patra; Stephen Sitch; Pierre Friedlingstein; Benjamin Poulter; Frederic Chevallier; Philippe Ciais; Josep G. Canadell; Ana Bastos; Ronny Lauerwald; Leonardo Calle; Kazuhito Ichii; et al. (Global Change Biology, 2020)
Robust estimates of CO 2 budget, CO 2 exchanged between the atmosphere and terrestrial biosphere, are necessary to better understand the role of the terrestrial biosphere in mitigating anthropogenic CO 2 emissions. Over the past decade, this field of research has advanced through understanding of the differences and similarities of two fundamentally different approaches: “top‐down” atmospheric inversions and “bottom‐up” biosphere models. Since the first studies were undertaken, these approaches have shown an increasing level of agreement, but disagreements in some regions still persist, in part because they do not estimate the same quantity of atmosphere–biosphere CO 2 exchange. Here, we conducted a thorough comparison of CO 2 budgets at multiple scales and from multiple methods to assess the current state of the science in estimating CO 2 budgets. Our set of atmospheric inversions and biosphere models, which were adjusted for a consistent flux definition, showed a high level of agreement for global and hemispheric CO 2 budgets in the 2000s. Regionally, improved agreement in CO 2 budgets was notable for North America and Southeast Asia. However, large gaps between the two methods remained in East Asia and South America. In other regions, Europe, boreal Asia, Africa, South Asia, and Oceania, it was difficult to determine whether those regions act as a net sink or source because of the large spread in estimates from atmospheric inversions. These results highlight two research directions to improve the robustness of CO 2 budgets: (a) to increase representation of processes in biosphere models that could contribute to fill the budget gaps, such as forest regrowth and forest degradation; and (b) to reduce sink–source compensation between regions (dipoles) in atmospheric inversion so that their estimates become more comparable. Advancements on both research areas will increase the level of agreement between the top‐down and bottom‐up approaches and yield more robust knowledge of regional CO 2 budgets.

Individual differences in neonatal white matter are associated with executive function at 3 years of age - Sarah J. Short; Michael T. Willoughby; Marie Camerota; Rebecca L. Stephens; Rachel J. Steiner; Martin Styner; John H. Gilmore (Brain Structure and Function, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Measuring Global Ocean Heat Content to Estimate the Earth Energy Imbalance - Benoit Meyssignac; Tim Boyer; Zhongxiang Zhao; Maria Z. Hakuba; Felix W. Landerer; Detlef Stammer; Armin Köhl; Seiji Kato; Tristan L’Ecuyer; Michael Ablain; John Patrick Abraham; Alejandro Blazquez; et al. (Frontiers in Marine Science, 2019)

Impacts of Shallow Lake Restoration on Vegetation and Breeding Birds in Iowa - Rachel A. Vanausdall; Stephen J. Dinsmore (Wetlands, 2019)

Effects of chronic cocaine self-administration and N-acetylcysteine on learning, cognitive flexibility, and reinstatement in nonhuman primates - Brian D. Kangas; Rachel J. Doyle; Stephen J. Kohut; Jack Bergman; Marc J. Kaufman (Psychopharmacology, 2019)

Graduating from food insecurity: evidence from graduation projects in Burundi and Rwanda - Stephen Devereux; Keetie Roelen; Ricardo Sabates; Rachel Sabates-Wheeler; Dimitri Stoelinga; Arnaud Dyevre (Food Security, 2019)

Separation, banking, and quality control of peripheral blood mononuclear cells from whole blood of melanoma patients - Martha Holland; Rachel Cunningham; Lake Seymour; Katja Kleinsteuber; Amy Cunningham; Tara Patel; Michael Manos; Ryan Brennick; Jun Zhou; F. Stephen Hodi; Mariano Severgnini (Cell and Tissue Banking, 2018)

Pulsatile interaction between the macro-vasculature and micro-vasculature: proof-of-concept among patients with type 2 diabetes - Rachel E. D. Climie; Dean S. Picone; Sarah Blackwood; Stuart E. Keel; Ahmad Qasem; Stephen Rattigan; James E. Sharman (European Journal of Applied Physiology, 2018)

Peromyscus leucopus mouse brain transcriptome response to Powassan virus infection - Luwanika Mlera; Kimberly Meade-White; Eric Dahlstrom; Rachel Baur; Kishore Kanakabandi; Kimmo Virtaneva; Stephen F. Porcella; Marshall E. Bloom (Journal of NeuroVirology, 2018)

A Review of the Tools Used for Marine Monitoring in the UK: Combining Historic and Contemporary Methods with Modeling and Socioeconomics to Fulfill Legislative Needs and Scientific Ambitions - Tim P. Bean; Naomi Greenwood; Rachel Beckett; Lauren Biermann; John P. Bignell; Jan L. Brant; Gordon H. Copp; Michelle J. Devlin; Stephen Dye; Stephen W. Feist; Liam Fernand; Dean Foden; et al. (Frontiers in Marine Science, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Alcohol consumption as a predictor of reactivity to smoking and stress cues presented in the natural environment of smokers - Rachel L. Tomko; Michael E. Saladin; Erin A. McClure; Lindsay M. Squeglia; Matthew J. Carpenter; Stephen T. Tiffany; Nathaniel L. Baker; Kevin M. Gray (Psychopharmacology, 2017)

Transcriptomic imprints of adaptation to fresh water: parallel evolution of osmoregulatory gene expression in the Alewife - Jonathan P. Velotta; Jill L. Wegrzyn; Samuel Ginzburg; Lin Kang; Sergiusz Czesny; Rachel J. O'Neill; Stephen D. McCormick; Pawel Michalak; Eric T. Schultz (Molecular Ecology, 2017)
Comparative approaches in physiological genomics offer an opportunity to understand the functional importance of genes involved in niche exploitation. We used populations of Alewife ( Alosa pseudoharengus ) to explore the transcriptional mechanisms that underlie adaptation to fresh water. Ancestrally anadromous Alewives have recently formed multiple, independently derived, landlocked populations, which exhibit reduced tolerance of saltwater and enhanced tolerance of fresh water. Using RNA ‐seq, we compared transcriptional responses of an anadromous Alewife population to two landlocked populations after acclimation to fresh (0 ppt) and saltwater (35 ppt). Our results suggest that the gill transcriptome has evolved in primarily discordant ways between independent landlocked populations and their anadromous ancestor. By contrast, evolved shifts in the transcription of a small suite of well‐characterized osmoregulatory genes exhibited a strong degree of parallelism. In particular, transcription of genes that regulate gill ion exchange has diverged in accordance with functional predictions: freshwater ion‐uptake genes (most notably, the ‘freshwater paralog’ of Na + /K + ‐ ATP ase α‐subunit) were more highly expressed in landlocked forms, whereas genes that regulate saltwater ion secretion (e.g. the ‘saltwater paralog’ of NKA α) exhibited a blunted response to saltwater. Parallel divergence of ion transport gene expression is associated with shifts in salinity tolerance limits among landlocked forms, suggesting that changes to the gill's transcriptional response to salinity facilitate freshwater adaptation.

Inadequacy of Palliative Training in the Medical School Curriculum - Nicholas Chiu; Paul Cheon; Stephen Lutz; Nicholas Lao; Natalie Pulenzas; Leonard Chiu; Rachel McDonald; Leigha Rowbottom; Edward Chow (Journal of Cancer Education, 2015)

Using scenarios to project the changing profitability of fisheries under climate change - Miranda C Jones; Stephen R Dye; John K Pinnegar; Rachel Warren; William W L Cheung (Fish and Fisheries, 2015)
Over‐exploitation and economic underperformance are widespread in the world's fisheries. Global climate change is further affecting the distribution of marine species, raising concern for the persistence of biodiversity and presenting additional challenges to fisheries management. However, few studies have attempted to extend bioclimatic projections to assess the socio‐economic impacts of climate‐induced range shifts. This study investigates the potential implications of changes in relative environmental suitability and fisheries catch potential on UK fisheries by linking species distribution modelling with cost‐benefit analyses. We develop scenarios and apply a multimodel approach to explore the economic sensitivity of UK fisheries and key sources of uncertainty in the modelling procedure. We projected changes in maximum potential catch of key species and the resulting responses in terms of net present value ( NPV ) over a 45‐year period under scenarios of change in fuel price, discount rate and government subsidies. Results suggest that total maximum potential catch will decrease within the UK EEZ by 2050, resulting in a median decrease in NPV of 10%. This value decreases further when trends of fuel price change are extrapolated into the future, becoming negative when capacity‐enhancing subsidies are removed. Despite the variation in predictions from alternative models and data input, the direction of change in NPV is robust. This study highlights key factors influencing future profitability of UK fisheries and the importance of enhancing adaptive capacity in UK fisheries.

Long‐term individual foraging site fidelity—why some gannets don't change their spots - Ewan D. Wakefield; Ian R. Cleasby; Stuart Bearhop; Thomas W. Bodey; Rachel D. Davies; Peter I. Miller; Jason Newton; Stephen C. Votier; Keith C. Hamer (Ecology, 2015)
Many established models of animal foraging assume that individuals are ecologically equivalent. However, it is increasingly recognized that populations may comprise individuals who differ consistently in their diets and foraging behaviors. For example, recent studies have shown that individual foraging site fidelity (IFSF, when individuals consistently forage in only a small part of their population's home range) occurs in some colonial breeders. Short‐term IFSF could result from animals using a win–stay, lose–shift foraging strategy. Alternatively, it may be a consequence of individual specialization. Pelagic seabirds are colonial central‐place foragers, classically assumed to use flexible foraging strategies to target widely dispersed, spatiotemporally patchy prey. However, tracking has shown that IFSF occurs in many seabirds, although it is not known whether this persists across years. To test for long‐term IFSF and to examine alternative hypotheses concerning its cause, we repeatedly tracked 55 Northern Gannets ( Morus bassanus ) from a large colony in the North Sea within and across three successive breeding seasons. Gannets foraged in neritic waters, predictably structured by tidal mixing and thermal stratification, but subject to stochastic, wind‐induced overturning. Both within and across years, coarse to mesoscale (tens of kilometers) IFSF was significant but not absolute, and foraging birds departed the colony in individually consistent directions. Carbon stable isotope ratios in gannet blood tissues were repeatable within years and nitrogen ratios were also repeatable across years, suggesting long‐term individual dietary specialization. Individuals were also consistent across years in habitat use with respect to relative sea surface temperature and in some dive metrics, yet none of these factors accounted for IFSF. Moreover, at the scale of weeks, IFSF did not decay over time and the magnitude of IFSF across years was similar to that within years, suggesting that IFSF is not primarily the result of win–stay, lose–shift foraging. Rather, we hypothesize that site familiarity, accrued early in life, causes IFSF by canalizing subsequent foraging decisions. Evidence from this and other studies suggests that IFSF may be common in colonial central‐place foragers, with far‐reaching consequences for our attempts to understand and conserve these animals in a rapidly changing environment.

Marine bacterioplankton community turnover within seasonally hypoxic waters of a subtropical sound: D evil's H ole, B ermuda - Rachel J. Parsons; Craig E. Nelson; Craig A. Carlson; Carmen C. Denman; Andreas J. Andersson; Andrew L. Kledzik; Kevin L. Vergin; Sean P. McNally; Alexander H. Treusch; Stephen J. Giovannoni (Environmental Microbiology, 2015)
Summary Understanding bacterioplankton community dynamics in coastal hypoxic environments is relevant to global biogeochemistry because coastal hypoxia is increasing worldwide. The temporal dynamics of bacterioplankton communities were analysed throughout the illuminated water column of D evil's H ole, B ermuda during the 6‐week annual transition from a strongly stratified water column with suboxic and high‐ pCO 2 bottom waters to a fully mixed and ventilated state during 2008. A suite of culture‐independent methods provided a quantitative spatiotemporal characterization of bacterioplankton community changes, including both direct counts and rRNA gene sequencing. During stratification, the surface waters were dominated by the SAR 11 clade of A lphaproteobacteria and the cyanobacterium S ynechococcus . In the suboxic bottom waters, cells from the order C hlorobiales prevailed, with gene sequences indicating members of the genera C hlorobium and P rosthecochloris – anoxygenic photoautotrophs that utilize sulfide as a source of electrons for photosynthesis. Transitional zones of hypoxia also exhibited elevated levels of methane‐ and sulfur‐oxidizing bacteria relative to the overlying waters. The abundance of both T haumarcheota and E uryarcheota were elevated in the suboxic bottom waters (> 10 9 cells l −1 ). Following convective mixing, the entire water column returned to a community typical of oxygenated waters, with E uryarcheota only averaging 5% of cells, and C hlorobiales and T haumarcheota absent.

Relaxed selection causes microevolution of seawater osmoregulation and gene expression in landlocked Alewives - Jonathan P. Velotta; Stephen D. McCormick; Rachel J. O’Neill; Eric T. Schultz (Oecologia, 2014)

Breast tumor cell TACE-shed MCSF promotes pro-angiogenic macrophages through NF-κB signaling - Stephen L. Rego; Rachel S. Helms; Didier Dréau (Angiogenesis, 2014)

Phylogeography and population history of Leopardus guigna, the smallest American felid - Constanza Napolitano; Warren E. Johnson; Jim Sanderson; Stephen J. O’Brien; A. Rus Hoelzel; Rachel Freer; Nigel Dunstone; Kermit Ritland; Carol E. Ritland; Elie Poulin (Conservation Genetics, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Examining the effects of initial smoking abstinence on response to smoking-related stimuli and response inhibition in a human laboratory model - Matthew P. Bradstreet; Stephen T. Higgins; F. Joseph McClernon; Rachel V. Kozink; Joan M. Skelly; Yukiko Washio; Alexa A. Lopez; Marie A. Parry (Psychopharmacology, 2014)

Effects of biocrusts and lichen-moss mats on plant productivity in a US sand dune ecosystem - Rachel K. Thiet; Alexis Doshas; Stephen M. Smith (Plant and Soil, 2014)

Quantification of Vibrio vulnificus in an Estuarine Environment: a Multi-Year Analysis Using QPCR - Jennifer J. Wetz; A. Denene Blackwood; J. Stephen Fries; Zachary F. Williams; Rachel T. Noble (Estuaries and Coasts, 2014)

Tumor necrosis factor-alpha-converting enzyme activities and tumor-associated macrophages in breast cancer - Stephen L. Rego; Rachel S. Helms; Didier Dréau (Immunologic Research, 2014)

A prospective open-label trial of paliperidone monotherapy for the treatment of bipolar spectrum disorders in children and adolescents - Gagan Joshi; Carter Petty; Janet Wozniak; Stephen V. Faraone; Andrea E. Spencer; K. Yvonne Woodworth; Rachel Shelley-Abrahamson; Hannah McKillop; Stephannie L. Furtak; Joseph Biederman (Psychopharmacology, 2013)

Interactions between VTA orexin and glutamate in cue-induced reinstatement of cocaine seeking in rats - Stephen V. Mahler; Rachel J. Smith; Gary Aston-Jones (Psychopharmacology, 2013)

Body mass index, tumor characteristics, and prognosis following diagnosis of early-stage breast cancer in a mammographically screened population - Aruna Kamineni; Melissa L. Anderson; Emily White; Stephen H. Taplin; Peggy Porter; Rachel Ballard-Barbash; Kathleen Malone; Diana S. M. Buist (Cancer Causes & Control, 2013)

2013 reviews of Global Change Biology - Stephen P. Long; Rachel Shekar (Global Change Biology, 2013)

ABO blood group and risk of epithelial ovarian cancer within the Ovarian Cancer Association Consortium - Elizabeth M. Poole; Margaret A. Gates; Brigit A. High; Stephen J. Chanock; Daniel W. Cramer; Julie M. Cunningham; Brooke L. Fridley; Simon A. Gayther; Ellen L. Goode; Edwin S. Iversen; Jolanta Lissowska; Rachel T. Palmieri Weber; et al. (Cancer Causes & Control, 2012)

River inflow, estuarine salinity, and Carolina wolfberry fruit abundance: linking abiotic drivers to Whooping Crane food - Jeffrey R. Wozniak; Todd M. Swannack; Rachel Butzler; Christopher Llewellyn; Stephen E. Davis (Journal of Coastal Conservation, 2012)

Ecosystem Carbon Remains Low for Three Decades Following Fire and Constrains Soil CO2 Responses to Precipitation in Southwestern Ponderosa Pine Forests - Christopher S. Ross; Jason P. Kaye; Margot W. Kaye; Valerie J. Kurth; Rachel Brimmer; Stephen C. Hart; Peter Z. Fulé (Ecosystems, 2012)

Decreased body weight in young Osterix-Cre transgenic mice results in delayed cortical bone expansion and accrual - Rachel A. Davey; Michele V. Clarke; Stephen Sastra; Jarrod P. Skinner; Cherie Chiang; Paul H. Anderson; Jeffrey D. Zajac (Transgenic Research, 2012)

An L 1-regularized logistic model for detecting short-term neuronal interactions - Mengyuan Zhao; Aaron Batista; John P. Cunningham; Cynthia Chestek; Zuley Rivera-Alvidrez; Rachel Kalmar; Stephen Ryu; Krishna Shenoy; Satish Iyengar (Journal of Computational Neuroscience, 2012)

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Effects on larval crabs of exposure to algal toxin via ingestion of heterotrophic prey - Rachel Garcia; Stephen Sulkin; Miranda Lopez (Marine Biology, 2011)

Phosphorus sources and demand during summer in a eutrophic lake - Amy M. Kamarainen; Rachel M. Penczykowski; Matthew C. Van de Bogert; Paul C. Hanson; Stephen R. Carpenter (Aquatic Sciences, 2009)

Bringing Out the Best in People: a Psychological Perspective - Rachel Kaplan; Stephen Kaplan (Conservation Biology, 2008)

Occupational toxicant inhalation injury: the World Trade Center (WTC) experience - Rafael E. de la Hoz; Michael R. Shohet; Rachel Chasan; Laura A. Bienenfeld; Aboaba A. Afilaka; Stephen M. Levin; Robin Herbert (International Archives of Occupational and Environmental Health, 2008)

Dynamics and predictive modelling of Vibrio spp. in the Neuse River Estuary, North Carolina, USA - Jennifer L. Hsieh; J. Stephen Fries; Rachel T. Noble (Environmental Microbiology, 2008)
Summary Vibrio spp. are naturally occurring bacteria in marine and estuarine environments around the world. The genus includes several human and animal pathogens that can negatively impact human health, seafood and aquaculture. Vibrio spp. populations are capable of rapid adaptation in response to changing environmental conditions, making them dynamic over short‐term and seasonal scales. Temperature, vertical mixing, tidal flushing, climate, precipitation and nutrient loading can change the estuarine environment and subsequently alter microbial community structure, including Vibrio spp., affecting estuarine water quality and public health. To describe these dynamics, Vibrio spp. concentrations and a range of microbial, physical and chemical measures were monitored every 2 weeks and after storm events for 19 months in the Neuse River Estuary (NRE). Results showed clear seasonal and geographic trends in Vibrio spp. abundance. Multiple regression analysis revealed a strong relationship to temperature and salinity, with additional minor influences of chlorophyll a and dissolved organic carbon. Similar models based on easily measured environmental parameters should be pursued for individual Vibrio species in the NRE and other estuarine environments. Predictive models provide useful information for managers, researchers and modellers of estuarine ecosystems.

New Cultivation Strategies Bring More Microbial Plankton Species into the Laboratory - Stephen Giovannoni; Rachel Foster; Michael Rappé; Slava Epstein (Oceanography, 2007)

Particle suspensions and their regions of effect in the Neuse River Estuary: Implications for water quality monitoring - J. Stephen Fries; Rachel T. Noble; Hans W. Paerl; Gregory W. Characklis (Estuaries and Coasts, 2007)

Erratum To: A Comparison of Alternative Strategies for Cost-Effective Water Quality Management in Lakes - Daniel Boyd Kramer; Stephen Polasky; Anthony Starfield; Brian Palik; Lynne Westphal; Stephanie Snyder; Pamela Jakes; Rachel Hudson; Eric Gustafson (Environmental Management, 2006)

Zooplankton retention in the estuarine transition zone of the St. Lawrence Estuary - Rachel D. Simons; Stephen G. Monismith; Ladd E. Johnson; Gesche Winkler; François J. Saucier (Limnology and Oceanography, 2006)
We used a three‐dimensional physical‐biological model consisting of a Eulerian circulation model and a Lagrangian particle‐tracking model, which included vertical sinking and swimming, to explore zooplankton retention in the estuarine transition zone of the St. Lawrence Estuary (SLETZ). To test the accuracy of the model, the results were temporally and spatially compared to a passive scalar released simultaneously in the circulation model and to field data for zebra mussel veligers. The model was then used to study the effects of baroclinic density‐driven flow, vertical sinking and swimming, and tidal vertical migration on retention of simulated zooplankton. Baroclinic flow, created by longitudinal and lateral salinity gradients, was a critical part of retention in the SLETZ. In the presence of baroclinic flow, vertical sinking and swimming speeds of $0.2 mm s21 had a large effect on the residence time of the simulated zooplankton as a result of gravitational circulation. Tidal vertical migration—a pattern of upward movement on flood and downward movement on ebb—was a viable retention mechanism for the SLETZ, and its effectiveness was amplified by baroclinic flow. As the speed of tidal vertical migration increased, the simulated zooplankton were concentrated in smaller areas of the SLETZ and moved further upstream.

Growth patterns of Carolina wolfberry (Lycium carolinianum L.) in the salt marshes of Aransas National Wildlife Refuge, Texas, USA - Rachel E. Butzler; Stephen E. Davis (Wetlands, 2006)

A Comparison of Alternative Strategies for Cost-Effective Water Quality Management in Lakes - Daniel Boyd Kramer; Stephen Polasky; Anthony Starfield; Brian Palik; Lynne Westphal; Stephanie Snyder; Pamela Jakes; Rachel Hudson; Eric Gustafson (Environmental Management, 2006)

Lipid-lowering actions of imidazoline antihypertensive agents in metabolic syndrome X - Rodney A. Velliquette; Rachel Kossover; Stephen F. Previs; Paul Ernsberger (Naunyn-Schmiedeberg's Archives of Pharmacology, 2006)

Haemodynamic responses to salbutamol and isometric exercise are altered in young adults with mild asthma - W Stephen Waring; Rachel B. Leigh (European Journal of Clinical Pharmacology, 2005)

Interactions among dissolved organic carbon, microbial processes, and community structure in the mesopelagic zone of the northwestern Sargasso Sea - Craig A. Carlson; Stephen J. Giovannoni; Dennis A. Hansell; Stuart J. Goldberg; Rachel Parsons; Kevin Vergin (Limnology and Oceanography, 2004)
At the Bermuda Atlantic Time‐Series Study (BATS) site, the field observations of dissolved organic carbon (DOC) dynamics indicate that seasonally produced “semilabile” DOC is resistant to rapid microbial degradation in the surface waters but available for microbial remineralization once it is delivered into the mesopelagic zone after convective overturn. In this study, we employed an experimental simulation of convective overturn events to determine whether the remineralization of semilabile DOC would occur in a controlled laboratory setting. Seawater culture experiments were conducted in which surface (≤10 m) and mesopelagic (250 m) 0.2‐mm filtrates were inoculated with unfiltered water from ≤10 and 250 m in an assortment of combinations to simulate various mixtures of nutrients, DOC quantity and quality, and microbial assemblages. Results indicate that (1) microbial inocula from the upper euphotic zone were incapable of remineralizing the seasonally accumulated semilabile DOC (µmol C L −1 resolution) on the timescales of the incubations; (2) the utilization of semilabile DOC was greatest when the inoculum source was from 250 m and the filtrate source was from the upper 10 m; and (3) the decrease in bacterioplankton diversity, estimated with the Shannon‐Wiener diversity index, was greater in treatments in which inoculum from 250 m was mixed with filtrate from 10 m than in treatments in which the surface inoculum was mixed with the surface filtrate. Our findings are that a portion of the surface semilabile DOC can be metabolized by microorganisms in a laboratory setting and that mesopelagic nutrients alone are insufficient to stimulate DOC drawdown >1.3 µmol L −1 . Transformations of microbial community structure were associated with the drawdown of surface DOC in simulated mixing events and suggest that microbial community structure is a factor in surface‐layer DOC dynamics.

Tritrophic Interactions Between Transgenic Potato Expressing Snowdrop Lectin (GNA), an Aphid Pest (Peach–Potato Aphid; Myzus Persicae (Sulz.) and a Beneficial Predator (2-Spot Ladybird; Adalia Bipunctata L.) - Rachel E. Down; Louise Ford; Stephen D. Woodhouse; Gillian M. Davison; Michael E.N. Majerus; John A. Gatehouse; Angharad M.R. Gatehouse (Transgenic Research, 2003)

Comparison of Beach Bacterial Water Quality Indicator Measurement Methods - Rachel T. Noble; Stephen B. Weisberg; Molly K. Leecaster; Charles D. McGee; Kerry Ritter; Kathy O. Walker; Patricia M. Vainik (Environmental Monitoring and Assessment, 2003)

A Regional Survey of the Microbiological Water Quality along the Shoreline of the Southern California Bight - Rachel T. Noble; John H. Dorsey; Molly Leecaster; Victoria Orozco-Borbón; Daniel Reid; Kenneth Schiff; Stephen B. Weisberg (Environmental Monitoring and Assessment, 2000)

Informatics for mutagenesis: the design of Mutabase—a distributed data recording system for animal husbandry, mutagenesis, and phenotypic analysis - Mark A. Strivens; Rachel L. Selley; Simon J. Greenaway; Mazda Hewitt; Xinhong Liu; Kirstin Battershill; Stefan L. McCormack; Karen A. Pickford; Lucie Vizor; Patrick M. Nolan; A. Jacqueline Hunter; Josephine Peters; et al. (Mammalian Genome, 2000)

Generating a Warm Glow: Lanthanide Complexes Which Luminesce in the Near-IR - Stephen Faulkner; Andrew Beeby; Rachel S. Dickins; David Parker; J. A. Gareth Williams (Journal of Fluorescence, 1999)

Stakeholder Perspectives on Appropriate Forest Management in the Pacific Northwest - Anne R. Kearney; Gordon Bradley; Rachel Kaplan; Stephen Kaplan (Forest Science, 1999)
One potential source of the controversy over forest management in the Pacific Northwest is differences in stakeholders' conceptualizations, or perspectives, on appropriate forest management. This study explores the nature of stakeholders' perspectives and identifies some of the differences and commonalities among them. Study participants included 23 individuals from 3 forest stakeholder groups: the USDA Forest Service, timber industry, and environmentalists. Participants' perspectives on appropriate forest management were assessed using a conceptual content cognitive map (3CM) task. Results indicate the existence of a wide range of concerns including issues related to the focus, setting, and process of management. The pattern of differences and similarities among stakeholder groups with respect to these concerns was found to be complex and to deviate substantially from common stereotypes. In addition, participants' perceptions of the other stakeholder groups were found to be highly stereotypical and were not supported by the data. For. Sci. 45(1):62-73.

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Analysis of axon tract formation in the zebrafish brain: the role of territories of gene expression and their boundaries - Stephen W. Wilson; Caroline Brennan; Rachel Macdonald; Michael Brand; Nigel Holder (Cell and Tissue Research, 1997)